New emerging entomopathogenic fungi isolated from soil in South Sumatra (Indonesia) and their filtrate and conidial insecticidal activity against Spodoptera litura - Siti Herlinda; Riski Anwar Efendi; Radix Suharjo; Hasbi Hasbi; Arum Setiawan; Elfita Elfita; Marieska Verawaty (Society for Indonesian Biodiversity, 2020)
Abstract. Herlinda S, Efendi RA, Suharjo R, Hasbi, Setiawan A, Elfita, Verawaty M. 2020. New emerging entomopathogenic fungi isolated from soil in South Sumatra (Indonesia) and their filtrate and conidial insecticidal activity against Spodoptera litura. Biodiversitas 21: 5102-5113. This study was carried out to confirm identity of Beauveria bassiana and Metarhizium anisopliae using sequence analysis of Internal Transcribed Spacer (ITS) region as well as the two unknown isolates of EPF and to investigate their filtrate and conidial insecticidal activity against S. litura larvae. The EPF species were identified based on morphological characters and molecular analysis. Their culture filtrate and conidial bioassays were performed on S. litura larvae. The species found were Penicillium citrinum (BKbTp), Talaromyces diversus (MSwTp1), B. bassiana (BSwTd4), and M. anisopliae (MSwTp3) and have been deposited in the GenBank. All EPF species have high insecticidal activity against S. litura larvae. The highest larvae mortality caused by filtrate was found on P. citrinum (98.67%) and not significantly different from those of T. diversus (96%), but significantly different from B. bassiana (86.67%) and M anisopliae (82.67%). The highest larvae mortality caused by the conidia was also occurred to P. citrinum (98.67%) which was not significantly different from those of T. diversus (97.33%), B. bassiana (86.67%), and M. anisopliae (86.67%). The LT50 caused by T. diversus filtrate was the shortest (6.19 days) and not significantly different from those caused by P. citrinum (6.62 days). The shortest LT50 caused by conidia was found on P. citrinum (5.45 days). Therefore, the conidia and filtrate of P. citrinum, a new emerging entomopathogenic fungus, has the highest insecticidal activity. P. citrinum has the potential to be developed into commercial mycoinsecticides.